Children’s Emotional Decelopment In The Fairy Tale Ṭāhir wa Nādia Based On Erik Erikson’s Theory Of Development - Siti Fatimah; M. Anwar Mas’adi (Program Studi Magister Pendidikan IPA, Universitas Mataram, 2026)
This study aims to analyze the emotional development of child characters in the fairy tale Ṭāhir wa Nādia by Amin Salama based on Erik Erikson’s psychosocial development theory and to examine its implications for children’s character formation. This study is significant because research on children’s literature is still predominantly characterized by descriptive approaches to moral values, while analyses of emotional development as a dynamic psychosocial process remain limited. Ṭāhir wa Nādia was selected because it narratively portrays children’s emotional experiences in extreme situations, such as fear, loss, hunger, and exposure to danger, which are highly relevant for analysis through Erikson’s developmental stages within the context of Middle Eastern religious culture. This research employs a qualitative descriptive method using reading and note-taking techniques. Primary data consist of narrative passages, dialogues, and characters’ actions, while secondary data are drawn from books and scholarly journals related to developmental psychology, children’s literature, and character education. The findings indicate that the emotional journeys of Ṭāhir and Nadia correspond to the first five stages of Erikson’s psychosocial development, namely trust, autonomy, initiative, industry, and early identity formation. Each stage generates adaptive responses that contribute to the emergence of character traits such as courage, independence, perseverance, empathy, cooperation, and moral and spiritual identity. The novelty of this study lies in the integration of emotional development analysis with a contextual reading of Erikson’s theory in Middle Eastern children’s fairy tales. These findings offer practical implications for parents and educators in utilizing fairy tales as a medium to support children’s emotional development and character education.